Hypocenter relocation to identify hidden faults and their environmental implications in the karst region of Maros-Pangkep, South Sulawesi - Wulur, Kevin Hanyu Clinton; Junaedi, Subaer; Susanto, Agus; Purba, Joshua; Priadi, Ramadhan (Journal of Degraded and Mining Lands Management, 2025)
The Maros-Pangkep region in South Sulawesi is a tropical karst landscape not officially mapped as an active fault zone, yet it has exhibited increasing micro-seismic activity in recent years. This study investigates the potential existence of hidden faults through hypocenter relocation using the double-difference method. A total of 191 earthquake events with magnitudes of 1-2.6 were successfully relocated using BMKG catalog data and the IASP91 global velocity model. The resulting hypocenters form a northwest–southeast-trending cluster, with fault plane geometry of 333°–346° strike, 8°–9° dip, and ~11 km length. These events cluster along boundaries of the Tonasa, Camba, and intrusive rocks, where competence contrast and karstification localize deformation. To complement the spatial analysis, magnitude–frequency characteristics were evaluated using the Gutenberg–Richter relationship. The estimated b-value of 1.34 indicates a low-stress regime dominated by small-magnitude seismicity, consistent with distributed deformation in brittle, heterogeneous lithologies. Although micro-seismic in scale, the spatial and statistical patterns suggest the presence of a structurally weak and potentially seismogenic zone that is not reflected in current tectonic maps. These findings underscore the importance of including the Maros–Pangkep region of South Sulawesi in seismic hazard assessments and land management efforts. The integration of relocation techniques and seismicity statistics proves effective for detecting latent fault structures in complex karst settings. In addition to seismic risks, such activity may accelerate land degradation through sinkholes, aquifer disruption, and ground instability, highlighting the value of geophysical assessments in managing vulnerable karst environments.